Association of changes in delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) with changes in cartilage thickness in the medial tibiofemoral compartment of the knee: a 2 year follow-up study using 3.0 T MRI. Issue 11 (19th July 2013) - Crema, Michel D; Hunter, David J; Burstein, Deborah; Roemer, Frank W; Li, Ling; Eckstein, Felix; Krishnan, Nitya; Hellio Le-Graverand, Marie-Pierre; Guermazi, Ali
Abstract : Objective: To determine the association between changes in the delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) index over 2 years as a measure of cartilage proteoglycan concentration, with changes in cartilage thickness in the medial tibiofemoral compartment of knees in middle-aged women. Methods: One hundred and forty-eight women (one knee for each subject) aged ≥40 years were included. 3.0 T MR images of the knee were acquired at baseline, 1 year and 2 years. Three-dimensional (3D) spoiled gradient recalled echo (SPGR) sequences (for cartilage thickness) and 3D inversion recovery-prepared SPGR sequences after dGEMRIC were acquired. Segmentation was performed in the medial central (weight-bearing) femur and tibia to determine cartilage proteoglycan concentration and thickness. The association of change in the dGEMRIC indices between baseline and 1-year follow-up with (a) concomitant changes in cartilage thickness and (b) change in cartilage thickness between 1 and 2 years was assessed using linear regression. Results: In the whole-sample model, a decrease in dGEMRIC indices over time at the central medial femur significantly predicted an increase in cartilage thickness at both the central medial femur (p=0.008) and the medial tibia (p=0.04). Conclusions: A decrease in dGEMRIC indices was associated with an increase in cartilage thickness in the medial compartment. Our results suggest that an increase in cartilage thickness may also be related to a decrease in proteoglycan concentration, which may represent swelling of cartilage in early stages of degeneration.